PREVALENCE OF HYPOSPADIAS IN THE POPULATION OF CHILDREN IN NAMANGAN - Mamasaliev N.S; Nurmatov Y.Kh; Alimov M.M; Mamasaliev Z.N; Usmonov B.U (Scholar Express Journals, 2025)
An analysis of available approaches to the management of patients with hypospadias was carried out, as well as some controversial issues regarding diagnosis in this category of patients. As available data show, surgical treatment of hypospadias has not yet led to the restoration of aesthetic and functional components, as a result of which the optimization of surgical treatment in modern conditions continues to remain relevant the task of pediatric reconstructive plastic surgery. Attention is paid to such areas as standardization of approaches to surgical treatment of hypospadias, unification of methods of urethroplasty and correction of penile curvature. Data from clinical studies on the use of various surgical techniques are presented.
Keywords: hypospadias; urethroplasty; penile malformation